(untitled) (Homoeopathy for All, 2021)
Inflammation of the sinuses rarely occurs without the parallel inflammation of the nasal mucosa and hence, a more accurate term for the inflammation of sinuses is Rhinosinusitis, rather than only sinusitis. Acute sinusitis is an inflammation of the paranasal sinuses and the nasal cavity lasting no longer than 4 weeks characterized by purulent nasal discharge (anterior, posterior or both) accompanied by nasal obstruction, facial pain pressure-fullness, or both. The term Acute sinusitis and Acute rhinosinusitis has been used interchangeably in literature are same entity and hence in the rest of the guidelines term Acute sinusitis is used.It is one of the most common conditions treated by primary care physicians and the fifth most common diagnosis for which antibiotics are prescribed. Most of the cases of acute rhinosinusitis is caused by viral infections associated with the common cold. The American Academy of Otolaryngology defines various subtypes of rhinosinusitis based on the duration of symptoms: -